Land Rental Markets: Experimental Evidence from Kenya - Acampora, Michelle; Casaburi, Lorenzo; Willis, Jack (American Economic Review, 2025)
Do land market frictions cause misallocation in agriculture? In a field experiment in western Kenya, we randomly subsidize owners to rent out land. Induced rentals mostly persist after the subsidy ends and increase output and value added, consistent with misallocation. Gains from trade arise from renters choosing higher-value crops, having higher productivity, and adopting more nonlabor inputs, while renters use similar quantities of labor as owners. Induced rentals are not those with the largest predicted gains, underlining the importance of the joint distribution of gains and frictions, with frictions arising from search, risk, and learning.(JEL C93, O13, O18, Q12, Q15, Q24, R52)